Pembrolizumab for Treating Relapsed or Refractory Classical Hodgkin Lymphoma: An Evidence Review Group Perspective of a NICE Single Technology Appraisal - Grimm, Sabine E. (Pharmacoeconomics, 2019)
As part of its Single Technology Appraisal (STA) process, the National Institute for Health and Care Excellence (NICE) invited the manufacturer (Merck Sharp & Dohme; MSD) of pembrolizumab (Keytruda(®)) to submit evidence of its clinical and cost effectiveness for the treatment of patients with relapsed or refractory classical Hodgkin lymphoma (RRcHL) who did not respond to treatment with brentuximab vedotin. Kleijnen Systematic Reviews Ltd, in collaboration with Maastricht University Medical Centre+, was commissioned to act as the independent Evidence Review Group (ERG). The ERG produced a detailed review of the evidence for the clinical and cost effectiveness of the technology, based on the company’s submission to NICE. According to the NICE scope, pembrolizumab was compared with single or combination chemotherapy. Comparisons were undertaken in two populations: patients who did and did not receive prior autologous stem cell transplant (autoSCT; populations 1 and 2, respectively). Despite it having been recommended by NICE in population 1 at the time the ERG received the company submission, nivolumab was not included as a comparator. No studies directly comparing pembrolizumab and its comparators were identified. One ongoing, single-arm study of the efficacy and safety of pembrolizumab (KEYNOTE-087) and one comparative observational study (Cheah et al., 2016) were used to inform the comparative effectiveness of pembrolizumab and standard of care (SoC), using indirect comparisons in both populations. Almost all analyses showed significant PFS and overall response rate benefits for pembrolizumab versus SoC, but due to being based on indirect comparison, were likely to contain systematic error. The economic evaluation therefore suffered from substantial uncertainty in any estimates of cost effectiveness. Furthermore, there was a lack of evidence on the uptake and timing of allogeneic stem cell transplant, and alternative assumptions had a significant impact on cost effectiveness. Immature survival data from KEYNOTE-087 exacerbated this issue and necessitated the use of alternative data sources for longer-term extrapolation of survival. Some issues identified in the company’s analyses were amended by the ERG. The revised ERG deterministic base-case incremental cost-effectiveness ratios based on the company’s second Appraisal Consultation Document response for pembrolizumab versus SoC (with a commercial access agreement) for populations 1 and 2 were £54,325 and £62,527 per quality-adjusted life-year gained, respectively. There was substantial uncertainty around these ICERs, especially in population 2. NICE did not recommend pembrolizumab as an option for treating RRcHL in population 1, but recommended pembrolizumab for use within the Cancer Drugs Fund in population 2.